Effects of alcohol intoxication goggles (fatal vision goggles) with a concurrent cognitive task on simulated driving performance. (17th November 2019) - Irwin, Christopher; Desbrow, Ben; McCartney, Danielle
Abstract: Objective: Fatal vision goggles (FVGs) are image-distorting equipment used to simulate alcohol impairment in driver education programs. Unlike alcohol, which disrupts cognitive processes, FVG only induces visual impairment. Performing concurrent cognitive tasks while wearing FVG may reduce the wearer's attentional resources and provide a better simulation of alcohol intoxication. This study examined the impact of wearing FVG with/without administration of a concurrent cognitive task on simulated driving. Methods: Twenty-one males (23 ± 3 y, mean ± SD) participated in this randomized, repeated-measures study involving two experimental trials. In each trial, participants completed a baseline drive then an experimental drive under one of two conditions: (1) FVG and (2) FVG with additional cognitive demand (FVG + CD). The driving test included 3 separate scenarios (Task 1, 2, 3) lasting ∼5min each. Lateral (standard deviation of lane position [SDLP]; number of lane crossings [LCs]) and longitudinal control parameters (average speed; standard deviation of speed [SDSP]; distance headway; minimum distance headway) were monitored in Tasks 1 and 2. Latency to two different stimuli (choice reaction time [CRT]) was examined in Task 3. Results: In Task 1, SDLP and LC were unaffected by either condition. However, SDSP increased significantly from baseline with FVG, irrespective of cognitive demand. In Task 2, distance headway decreased significantly from baseline with FVG, but increased significantly with FVG + CD. Minimum distance headway was significantly decreased, while SDLP increased significantly and LC increased (although not statistically significant) in both conditions relative to baseline. In Task 3, a significant increase in CRT occurred with FVG + CD, but not with FVG alone. Conclusions: Wearing FVG negatively impacted simulated driving performance. However, effects were isolated to specific performance outcomes and were dependent on complexity of the driving task. Addition of a secondary cognitive task exacerbates the effects of FVG on select driving outcomes (i.e. lane position, SDSP), influences the effect direction on other measures (i.e. distance headway), and has a detrimental effect on reaction time to stimuli embedded in the scenario, that is not observed with FVG alone. Future studies using FVG as a surrogate means to alcohol intoxication should consider these results, informing methodological decisions to reduce potential for confounding effects.